Perbandingan Hukum Perkawinan Antara Mesir dan Malaysia dalam Aspek Perkawinan ‘Urfi: Status, Pengakuan, dan Perlindungan Hak - Dewifa Winanda; Sulafah Deifa Fazaroh Adhellia; Nabiela Naily (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
'Urfi marriage is a practice of unofficial marriage that is recognized religiously but not recorded by the state. This phenomenon becomes a legal issue in various Muslim countries, including Egypt and Malaysia, which have different approaches. This article aims to compare the legal status of ‘Urfi marriage in Egypt and Malaysia, analyze its implications for the protection of women's and children's rights, and examine the legal proof consequences due to the lack of registration of such marriages. Using a normative-comparative legal research method with legislative and conceptual approaches, this study analyzes primary legal instruments from both countries as well as fiqh literature and relevant jurisprudence. Research results show that Egypt recognizes ‘Urfi marriages as legally valid in terms of religion but has required registration since 2000, whereas Malaysia does not legally recognize ‘Urfi marriages because they do not meet mandatory registration requirements. This difference has a significant impact on protecting wives' rights regarding alimony, children's identity, inheritance, and protection from domestic violence. This study concludes that the lack of registration in ‘Urfi marriages weakens the legal position of women and children, so there is a need to harmonize religious law and civil law to ensure substantive justice.